Comparative Study Of Bs8110 And Eurocode 2 Standards For Design Of A Factory Reinforced Concrete Flat Slab - Chong, Hong Rui (Universiti Sains Malaysia, 2018)
This project provides some fundamental background of the European Structural Codes (Eurocodes) and some introductory aspects particularly on design principles and the differences with British Standard Codes brought about by the harmonised codes. This project also investigates and compares the use of BS 8110 and Eurocode 2 in the design of reinforced concrete flat slab to determine the differences between the two codes for this project. The scope of this research is designing principles for slab design by using the Equivalent Frame Method. The loading and analysis are taken from the slab structure that is loaded with track trench, analysed and detailed design results made based on the analysis results. The building adopted for this project is a factory building; the Scandinavian Industrialised Building System (SIBS) Precast Building Components Factory. The building is a one-storey building consisting of ground floor with steel deck roof. The ground floor consists of production and storage area. The building is about 5m high having an approximate plan dimension of 110m x 46m. The British Standard Design reinforcement bars strength and unit weight of reinforced concrete are slightly less than that of Eurocode 2 Design. The result of concrete cover needed for Eurocode 2 Design is more than that of British Standard Design due to more fire resistance characteristics. The reinforcement area for both span middle strip and column strip as well as support middle strip and column strip of British Standard Design is less than that of Eurocode 2 Design. However, the British Standard Design using BRC A10 wire mesh need to provide full yield strength lap length causing the reinforcement area provided increases to 569.9 mm2. The cost of concrete needed for Eurocode 2 Design is higher than that of British Standard Design based on the designed concrete cover thickness. Lastly, the cost of steel reinforcement bars needed for Eurocode 2 Design is lower than that of British Standard Design according to the designed steel reinforcement bars area provided.